Implementation of the Poverty Reduction Acceleration Policy in Karawang Regency, Indonesia - Mu'min Ma'ruf (Institut Pemerintahan Dalam Negeri, 2022)
Poverty is a serious problem that needs to be urgently overcome because its vulnerability does not only impact the environment but can also affect the resilience of the nation and state. The need to eradicate poverty led to the implementation of Regional Regulation No. 2 of 2014 concerning poverty alleviation acceleration by the Karawang Regency Government. Therefore, this research aims to describe and analyze these policies to boost the economy. Data were collected through observation, documentation, and in-depth interviews with 23 respondents consisting of 3 regulators, 8 implementers, and 12 locals. The results showed that the impact of implementing the policy is in accordance with the addition of educational infrastructure, expansion of access to education, quality education, increase in school participation rates, rise in the expected length of schooling, and increase in literacy rates. The change level in policy implementation includes a decrease in the number of elementary and junior high school teachers with a high school or associate degree and the number of dropouts, an increase in students’ participation rates, and a reduction in the poor population. In conclusion, the policy implementation to accelerate poverty reduction in education positively impacts the rate of change and acceptance of the poor community. However, some implementers are less sympathetic in carrying out their duties. Finally, the optimal policy implementation model for accelerating poverty reduction in the education sector can be constructed by looking at the configuration and collaboration between regulatory actors, implementers, and beneficiaries. Keywords: Poverty Alleviation; Policy; Implementation Abstrak Kemiskinan merupakan persoalan serius dan mendesak untuk ditanggulanggi. Kerentanan yang ditimbulkan akibat kemiskinan tidak hanya berdampak pada lingkungan, namun dapat meluas mempengaruhi ketahanan bangsa dan negara. Untuk itu Pemerintahan Kabupaten Karawang membuat kebijakan yang tertuang dalam Perda Nomor 2 Tahun 2014 tentang percepatan penanggulangan kemiskinan. Studi ini bertujuan untuk mendeskripsikan dan menganalisis bagaimana implementasi kebijakan percepatan penanggulangan kemiskinan bidang pendidikan di Kabupaten Karawang. Penulis mengumpulkan data melalui observasi, dokumentasi dan wawancara secara mendalam terhadap 23 orang responden yang terdiri dari regulator 3 orang, implementor 8 orang, dan masyarakat 12 orang. Hasil penelitian menunjukan bahwa dampak implementasi kebijakan adalah penambahan sarana prasarana pendidikan, perluasan /pemerataan akses pendidikan, peningkatan mutu pendidikan, peningkatan angka partisipasi sekolah, peningkatan angka harapan lama sekolah/rata-rata lama sekolah dan peningkatan angka melek huruf. Adapun tingkat perubahan dalam implementasi kebijakan meliputi penurunan jumlah guru SD dan SMP, terjadi peningkatan angka partisipasi sekolah, masih adanya jumlah anak yang putus sekolah, dan terjadi penurunan jumlah penduduk miskin. Penulis menyimpulkan bahwa implementasi kebijakan percepatan penanggulangan kemiskinan bidang pendidikan mempunyai dampak, tingkat perubahan dan penerimaan masyarakat miskin yang baik, meskipun masih adanya oknum implementor yang kurang simpatik dalam menjalankan tugasnya. Adapun model Implementasi kebijakan yang optimal dalam percepatan penanggulangan kemiskinan bidang pendidikan dapat dikonstruksi dengan melihat konfigurasi dan kolaborasi antar aktor regulator, implementor dan penerima manfaat. Kata Kunci: Penanggulangan Kemiskinan; Kebijakan; Implementasi